Antifungal resistance and poor clinical outcome rates of Candida auris in mainland China: A systematic review and meta-analysis - Tao Xu; Rui Wang; Yufang Gao; Lei Yang (Frontiers in Microbiology, 2026)
Objective This study systematically evaluated the antifungal resistance profile of Candida auris ( C. auris ) to five antifungal agents in mainland China, and analyzed clinical outcomes in a combined cohort of patients with C. auris colonization or infection. It aims to provide evidence-based references for clinical antifungal management and nosocomial infection prevention and control. Methods Six databases, including PubMed, Web of Science, and Embase, were systematically searched to identify observational studies reporting antifungal susceptibility of C. auris isolates and clinical outcomes of corresponding patients in mainland China. Meta-analysis was adopted to pool the resistance rates and multidrug resistance (MDR) rate of five antifungal agents. Meanwhile, we summarized the overall rate of poor prognosis, in-hospital mortality rate, and rate of clinical deterioration at discharge for patients with detected C. auris . Funnel plots and Egger’s test were used to assess publication bias. Results C. auris in mainland China exhibited extremely high resistance to fluconazole, with a pooled resistance rate of 98% (95%CI: 93%–100%). Echinocandins maintained favorable overall susceptibility. The resistance rates of caspofungin, micafungin, and anidulafungin were 3% (95%CI: 0%–11%), 2% (95%CI: 0%–4%), and 1% (95%CI: 0%–3%), respectively. The resistance rate of C. auris to amphotericin B was 34% (95%CI: 12%–61%). The pooled MDR rate was 60% (95% CI: 16%–97%). The overall poor prognosis rate of patients with C. auris isolation was 43% (95%CI: 23%–64%). The in-hospital mortality rate was 24% (95% CI: 12%–38%), while the rate of clinical deterioration at discharge was 23% (95% CI: 5%–46%). No significant publication bias was observed in this study. Conclusion Fluconazole is not an appropriate choice for treating C. auris strains in mainland China, while echinocandins should be the primary treatment option. Amphotericin B should be administered cautiously based on antifungal susceptibility testing. The pooled MDR rate was relatively high. Patients with C. auris colonization or infection exhibit variable clinical outcomes. Clinical practice should prioritize routine laboratory antifungal susceptibility surveillance, standardized hospital infection control measures, and targeted interventions to improve patient clinical outcomes.